The man who mistook his neuropsychologist for a popstar: when configural processing fails in acquired prosopagnosia - Jansari, Ashok; Miller, Scott; Pearce, Laura; Cobb, Stephanie; Sagiv, Noam; Williams, Adrian; Tree, Jeremy; Hanley, Rick (Frontiers in Human Neuroscience, 2015)
We report the case of an individual with acquired prosopagnosia who experiences extreme difficulties in recognising familiar faces in everyday life despite excellent object recognition skills. Formal testing indicates that he is also severely impaired at remembering pre-experimentally unfamiliar faces and that he takes an extremely long time to identify famous faces and to match unfamiliar faces. Nevertheless, he performs as accurately and quickly as controls at identifying inverted familiar and unfamiliar faces and can recognise famous faces from their external features. He also performs as accurately as controls at recognising famous faces when fracturing conceals the configural information in the face. He shows evidence of impaired global processing but normal local processing of Navon figures. This case appears to reflect the clearest example yet of an acquired prosopagnosic patient whose familiar face recognition deficit is caused by a severe configural processing deficit in the absence of any problems in featural processing. These preserved featural skills together with apparently intact visual imagery for faces allow him to identify a surprisingly large number of famous faces when unlimited time is available. The theoretical implications of this pattern of performance for understanding the nature of acquired prosopagnosia are discussed.